Weird Behaviour of Peter: An Existentialist study on Jostein Gaarder's The Ringmaster's Daughter Novel (2001) - Nurjanah, Niftah, Dr. Abdilah Nugroho, M. Hum (2017)
The study is aimed at analysing weird behaviour of Petter on Jostein Gaarder'sThe Ringmaster's Daughter novel (2001) by existentialist theory. This study belongs to qualitative research. The technique of the data collection of this research is library research and technique of data analysis of this research are clarifying the obtained data by selecting the necessary one and analyzing data based on existentialist theory by Sartre. The results of this analysis show: 1) The indicators of Petter's weird behaviour are: a) He cannot give response or reacts normally; b) He was afraid to affect with emotional condition; c) He interacts with his imaginary; d) He cannot focus to finish his story, and sells his plots to other writers; 2) The cause of weird behaviour is his childhood trauma; 3) The impacts of weird behaviour are: a) He becomes an unsociable man; b) He has an imaginary friend; c) He never finished his stories; d) He does not like to be famous, a novelist, and get influence with the other; 4) The author of this novel addresses some issues related to human existence that people at any level of age can read this. This novel shows that man is an effect maker for others and man is free creating himself because freedom is the essence of human being. Keyword: traumatic experience, weird behaviour, freedom, existentialist